1999
DOI: 10.1161/01.res.84.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Very Late Antigen-4 Integrin Decreases Leukocyte Entry and Fatty Streak Formation in Mice Fed an Atherogenic Diet

Abstract: —Atherosclerotic lesion development is characterized by the recruitment of leukocytes, principally monocytes, to the vessel wall. Considerable interest has been focused on the adhesion molecule(s) involved in leukocyte/endothelial interactions. The goal of the present study was to determine the role of the very late antigen-4 (VLA-4) integrin/ligand interaction in fatty streak development using murine models. Because α4 null mice are not viable, a peptidomimetic was used to block VLA-4–mediated leukocyte bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 48 publications
2
60
0
1
Order By: Relevance
“…33 However, binding of monocytes to OxPAPC-stimulated endothelial cells is mediated by CS-1 fibronectin 34 and blocking CS-1 reduced atherosclerotic lesion formation in mice. 35 In addition to expression of chemokines, we found that OxPAPC induced expression of several other atherosclerosis-related genes. We demonstrate that oxidized phospholipids induce IL-6 transcripts in a native murine artery in vivo.…”
Section: Discussionmentioning
confidence: 76%
“…33 However, binding of monocytes to OxPAPC-stimulated endothelial cells is mediated by CS-1 fibronectin 34 and blocking CS-1 reduced atherosclerotic lesion formation in mice. 35 In addition to expression of chemokines, we found that OxPAPC induced expression of several other atherosclerosis-related genes. We demonstrate that oxidized phospholipids induce IL-6 transcripts in a native murine artery in vivo.…”
Section: Discussionmentioning
confidence: 76%
“…This was further supported by evidence that chronic application of a small peptide that inhibits ligand binding by α 4 β 1 delays the development of atherosclerosis in mice fed an atherogenic diet (7). However, interpretation of this study was complicated by the fact that activated endothelial cells can express a second ligand for α 4 β 1 integrin, alternatively spliced fibronectin containing the CS-1 peptide.…”
mentioning
confidence: 59%
“…R-Ras was shown to activate PI3K, which then results in the activation of α5β1 integrin on the apical surface; this activated integrin binds the fibronectin 18 . In fact, it has been shown that inactivation of VLA-4 using a synthetic peptide mimetic of CS1 ( 4 ), decreased leukocyte entry and fatty streak formation in mice fed an atherogenic diet ( 19,20 ). Recent findings have also demonstrated a role for the prostaglandin receptor E2 (EP2), a G-protein coupled receptor (GPCR), in this pathway (Figure 1) 21 .…”
Section: Monocyte Bindingmentioning
confidence: 99%